Consumer behavioural intention and perception towards organic foods in national capital of India - SATYAPRIYA, SATYAPRIYA; SINGH, PREMLATA; SANGEETHA, V.; PAUL, SUDIPTA; BARUA, SUKANYA; MATHUR, PULKIT; RATHORE, HIMANSHI; KESHAVA, KESHAVA (The Indian Journal of Agricultural Sciences, 2019)
Organic food products are gaining popularity among consumers because of improved awareness about health, and protection of the environment. Though the organic food market is keen today but to broaden it further, one must understand consumersâ€™ perception for organic products. In this study, consumersâ€™ behavioural intention and perception was studied towards purchase of organic food. Structured questionnaires were formulated and 1047 respondents residing in the urban sectors of Delhi were approached. The reliability analysis of questionnaires carried out using the Cronbach’s Alpha test indicated that for the tested variables i.e. Attitude, Subjective norms and Perceived Behaviour Control (PBC), the value calculated was approx. 0.90. Further, theory of planned behaviour (TPB) applied to the study showed 78% variance amongst the above stated three variables towards the behavioral intention of the consumers for organic food, and PBC was the most impactful variable to affect the overall intention of the consumersâ€™ to purchase organic products. Price value, followed by the origin and freshness of the produce were some of the important factors contributing in decision making. Moreover, consumers prefer to purchase organic foods if they are not very expensive in comparison to the conventional ones. The results provided in-depth insight about the consumersâ€™ behavioural intentions, knowledge, perception and factors contributing to the purchase behavior of organic food commodities by the Indian urban population.